2013
DOI: 10.1371/annotation/5b4e222a-a9bc-4036-882e-cd975301ca89
|View full text |Cite
|
Sign up to set email alerts
|

Correction: The MEK-ERK Pathway Is Necessary for Serine Phosphorylation of Mitochondrial STAT3 and Ras-Mediated Transformation

Abstract: Activating mutations in the RasGTPases are the most common oncogenic lesions in human cancer. Similarly, elevated STAT3 expression and/or phosphorylation are observed in the majority of human cancers. We recently found that activated Ras requires a mitochondrial rather than a nuclear activity of STAT3 to support cellular transformation. This mitochondrial activity of STAT3 was supported by phosphorylation on serine 727 (S727) in the carboxyl-terminus of STAT3. In this study we show that the H-Ras oncoprotein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…The importance of phosphorylated STAT3 S727 (pSTAT3 S727 ) has been observed; pSTAT3 S727 is highly enriched in mitochondria than that present in the cytoplasm [42,43], and the activities of mitochondrial STAT3 (mitoSTAT3) are supported by phosphorylation on STAT3 S727 [43]. The discovery of mitoSTAT3 opened up a new avenue through which STAT3 may regulate cell metabolism and mitochondrial gene expression [42,44].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of phosphorylated STAT3 S727 (pSTAT3 S727 ) has been observed; pSTAT3 S727 is highly enriched in mitochondria than that present in the cytoplasm [42,43], and the activities of mitochondrial STAT3 (mitoSTAT3) are supported by phosphorylation on STAT3 S727 [43]. The discovery of mitoSTAT3 opened up a new avenue through which STAT3 may regulate cell metabolism and mitochondrial gene expression [42,44].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, post-translational modifications activated downstream of cytokines, growth factors and oncogenes shape the sub-cellular localization and activities of STAT3 both in cancer and normal cells. In addition to Y705P, STAT3 can also undergo several other post-translational modifications such as phosphorylation on S727 in oncogenic transformation [79,80], lysine acetylation or methylation and cysteine oxidation or glutathionylation in starved cancer cells stimulated with serum or insulin, and in cardiomyocytes as part of reduction-oxidation (REDOX) regulation [81][82][83]. Serine 727 phosphorylated STAT3 (pS727 STAT3) exhibits distinct mitochondrial localization and non-transcriptional function through the modulation of the activity of the electron transport chain (ETC) and the mitochondrial permeability transition pores (MPTP) [1,84].…”
Section: Mitochondrial Stat3: Inside the Engine Corementioning
confidence: 99%
“…Direct mitochondrial metabolic remodeling through the activity of STAT3 was shown via the serine phosphorylation of mitochondrial STAT3; a RAS/MEK/ERK mediated transformation in a mouse model through the modulation of aerobic glycolysis and ETC activity [79,91]. The nuclear influence of canonically activated STAT3 on metabolism was shown to promote a shift towards glycolysis through HIF-1α-induced pyruvate kinase M2 isoform (PKM2) chronic activation of STAT3; this in turn activates HIF-1α; this positive feedback loop supports proliferative and pro-survival phenotypes [48,49,99].…”
Section: Metabolic Remodelling Through Stat3 Stimulationmentioning
confidence: 99%
“…Tumor Necrosis Factor Receptor-2 (TNFR2), via Janus Kinase (JAK), is the most relevant mediator of STAT3 activation in cardiomyocyte [68,69,70,71,72]. Moreover, it has been reported that the activation of ERK [40,41] and the inhibition of Forkhead Box O-1 (FOXO-1) [69] contribute to the cross-talk between the RISK and the SAFE pathway [73,74]. However, as the SAFE pathway in humans is under the control of STAT5, the role of STAT3 in this pathway is still a matter of debate [75].…”
Section: Cardioprotective Pathwaysmentioning
confidence: 99%